Most relevant apotheosis of women in Physiological Sciences - Salgado Rodríguez, Jennifer; Reytor Vega, José Alcides (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: For a long time, science was considered a topic only for men, while women were assigned to household chores. Objective: highlighting the contribution check about outstanding women in Physiology. Materials and methods: A bibliographic check about outstanding women in Physiology was carried, the documentation available in the libraries of the medical institutions, as the ones in the University of Medical Sciences, and the INFOMED database were revised, gathering around 32 bibliographic references. Results: Prominent women like Birte Marie Krogh, Gerty Cori, Bárbara McClintock, Linda B. Buck, May-Britt Moser won Nobel Prizes in Medicine and Physiology. It is also very commendable the acting of those who teach or do some research on any subject of interest. Conclusions: Their contributions are examples of women´s capacity and willingness for standing on top places in sciences, even in temporary or special adverse conditions in comparison to men. This last matter is still a topic of discussion in order to gain the same rights.